Konstruksi Makna Nikah Muda pada Pasangan Nikah Muda di Jawa Barat - Gianni Fathin Rabbani - (UNISBA Press, 2022)
Abstract.In Islam, it is obligatory to marry when you are physically and mentally able,but if you are not able to carry out marriage, it is recommended to replace the restraintof lust, namely by fasting. Young marriage is a phenomenon that is familiar inIndonesia, especially in Indonesia. West Java is one of the biggest contributors to thenumber of young marriages in Indonesia, especially Sukabumi which has the highestnumber of young marriages in West Java. Data shows that young marriages are oneof the biggest contributors to the divorce rate in Indonesia, but not all young marriagesend in divorce. There are many factors that cause young marriage, namely religion,economy, customs and culture. This study discusses how the meaning of marryingyoung is reconstructed by the perpetrators of young marriages themselves. The studyused by researchers is a phenomenological study to find out the meaning, motives andexperiences of young marriage actors. Data collection techniques were carried out bymeans of observation, interviews, and literature study. Researchers used the PurposiveSampling Technique because it matched what the researchers needed, namely sourceswhose criteria had been determined and in accordance with the phenomenon understudy, namely young marriage. In this study, the negative meaning of young marriagein general terms can be reconstructed by students who marry young in Sukabumi City.Keywords: Meaning construction, Phenomenological Studies, The meaning of youngmarriageAbstrak. Dalam agama islam wajib hukumnya untuk melakukan pernikahan bila sudahmampu baik lahir maupun batin, akan tetapi bila belum mampu melaksanakanpernikahan maka dianjurkan untuk mengganti penahan gejolak nafsu yaitu dengan caraberpuasa.Pernikahan muda merupakan sebuah fenomena yang sudah tidak asing lagidi Indonesia yang khususnya di Jawa Barat yang menjadi salah satu penyumbang angkaterbesar pernikahan muda di Indonesia, khususnya Sukabumi yang memiliki angkapernikahan muda tertinggi di Jawa Barat. Data menunjukan bahwa pernikahan mudamenjadi salah satu penyumbang angka terbesar perceraian di Indonesia, akan tetapitidak semua pernikahan muda berakhir dengan perceraian Adapun yang masih bertahansampai sekarang. Ada banyak faktor penyebab pernikahan muda yaitu agama,ekonomi, adat dan budaya. Penelitian ini membahas bagaimana makna menikah mudayang dikonstruksi ulang oleh pelaku pernikahan muda itu sendiri. Studi yang digunakanpeneliti ialah studi fenomenologi guna mengetahui makna, motif dan pengalaman daripelaku pernikahan muda. Teknik pengumpulan data dilakukan dengan cara observasi,wawancara, dan studi kepustakaan. Peneliti menggunakan Teknik Purposive Samplingkarena cocok dengan yang peneliti butuhkan yaitu narasumber yang sudah ditentukankriterianya dan sesuai dengan fenomena yang diteliti yaitu menikah muda. Dalampenelitian ini makna menikah muda yang negatif di kacamata umum bisadirekonstruksi ulang oleh mahasiswa yang menikah muda di Kota Sukabumi.Kata kunci: Konstruksi Makna, Studi Fenomenologi, Makna Pernikahan Muda